Pengaruh Store Atmosphere dan Kualitas Produk Terhadap Kepuasan Konsumen Navila Cafe - Maghfirotur Rofi’ah (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2020)
Competition that occurs at this time makes entrepreneurs to create characteristics that will make consumers interested in these characteristics, characteristics that will be made can be from the store atmosphere or product quality that will later make consumers make repeat purchases. Navila Cafe is a culinary and lifestyle business that has an interesting and unique atmosphere that will make consumers comfortable visiting there, Navila also provides a variety of food and beverage products that will make consumers satisfied when enjoying food at Navila Cafe. This study aims to determine the effect of store atmosphere and product quality on consumer satisfaction Navila Cafe Jombang. This type of research is quantitative descriptive using survey methods. The number of samples in this study were 30 with a purposive sampling technique. Analysis of the data used is the validity and reliability test, the classic assumption test, and the hypothesis test with the multiple linear regression formula. The results in this study indicate that there is an influence between store atmosphere and product quality on consumer satisfaction of Navila Cafe Jombang either partially or simultaneously with a contribution of 86.7% while the remaining 13.3% is influenced by other factors.